Pendekatan Historis dan Pragmatis Industri dan IKM di Kota Gresik - Reza Akbar Mauliza; Inggrid Debby Ekza Veronica; Muhammad Yasin (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Efforts to develop the industrial sector in a country or region is an Industrialization strategy. The goal of this strategy is to increase the production of goods and services more efficiently and effectively, so as to increase economic growth and reduce dependence on other economic sectors such as agriculture or services. The historical approach emphasizes the use of economic policies based on historical experience and national economic traditions to build national industries. While the pragmatic approach focuses more on using practical actions to improve industrial conditions and the national economy and accelerate the industrialization process.